2013
DOI: 10.1152/ajprenal.00376.2012
|View full text |Cite
|
Sign up to set email alerts
|

Analogs of bardoxolone methyl worsen diabetic nephropathy in rats with additional adverse effects

Abstract: Bardoxolone methyl is an antioxidant inflammation modulator acting through induction of Keap1-Nrf2 pathway. Results from a recent phase IIb clinical trial reported that bardoxolone methyl was associated with improvement in the estimated glomerular filtration rate in patients with advanced chronic kidney disease and Type 2 diabetes. However, increases in albuminuria, serum transaminase, and frequency of adverse events were noted. We studied the effect of 3-mo treatment with RTA 405, a synthetic triterpenoid ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
88
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(99 citation statements)
references
References 29 publications
8
88
3
Order By: Relevance
“…This was associated with attenuation of oxidative stress, inflammation, and glomerular and tubulo-interstitial lesions, and partial improvement of renal function confirming the results of recent studies (30)(31)(32). In contrast, dh404 treatment at 10 mg/kg/day dosage resulted in intensification of proteinuria, deterioration of renal function and histological lesions, and amplification of oxidative stress and inflammation, confirming the effects observed in the Zucker rats with diabetic nephropathy and ApoE deficient mice with streptozoticineinduced diabetes [29,33]. Taken together these findings indicate the dose dependent dimorphic actions of Bardoxolone methyl analogs on CKD progression with favorable effect at a low drug dosage and toxic effects at a high dosage.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This was associated with attenuation of oxidative stress, inflammation, and glomerular and tubulo-interstitial lesions, and partial improvement of renal function confirming the results of recent studies (30)(31)(32). In contrast, dh404 treatment at 10 mg/kg/day dosage resulted in intensification of proteinuria, deterioration of renal function and histological lesions, and amplification of oxidative stress and inflammation, confirming the effects observed in the Zucker rats with diabetic nephropathy and ApoE deficient mice with streptozoticineinduced diabetes [29,33]. Taken together these findings indicate the dose dependent dimorphic actions of Bardoxolone methyl analogs on CKD progression with favorable effect at a low drug dosage and toxic effects at a high dosage.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore due to increased mortality from congestive heart failure the multi-center, randomized, placebo-controlled, Phase 3 clinical trial of a bardoxolone methyl analog in type 2 diabetic patients with stage 4 CKD (BEACON trial) was terminated [28]. Finally in a recent study Zoja et al [29] found substantial weight loss, anorexia, liver injury, exacerbation of proteinuria, dyslipidemia, glomerulosclerosis, and tubular damage with long term administration of the bardoxolone analogues, RTA 405 (50 and 100 mg/kg/day) and dh404 (5 and 25mg/kg/day) in obese Zucker rats with type-2 diabetes and nephropathy. These observations raised doubt about the potential efficacy of the bardoxolone methyl analogs in Type 2 diabetic nephropathy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 On the other hand, in Zucker diabetic fatty rats, a model of type 2 diabetes mellitus with progressive renal disease treatment with RTA 405, a bardoxolone analogue, caused worsening of proteinuria, glomerulosclerosis, and tubular damage. 24,25 Clinical studies have also shown discordant results. In the phase II Trial to Determine the Effects of Bardoxolone Methyl on eGFR in Patients With Type 2 Diabetes and Chronic Kidney Disease (BEAM study), patients with chronic kidney disease treated with bardoxolone had significantly improved renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, triterpenoid analogue, bardoxolone methyl, showed improved renal function in early-stage chronic kidney disease in type 2 diabetes; however, Phase III clinical trial with this compound for very severe-stage patients was halted due to undisclosed safety issues (Reata Phamaceuticals) (Clinical Trials.gov; NCT01351675). Moreover, the recent study by Zoja et al has shown that bardoxolone analogues are ineffective in curing diabetic nephropathy in Zucker diabetic fatty rats but instead, the rats receiving such analogues worsen the outcome of the disease (476). While the CDDO-Im potently activates Nrf2 target genes in multiple tissues, proteomic analysis recently revealed that this CDDO-Im interacts with *600 different proteins, including many different transcription factors (464).…”
Section: E Regulation Of Antioxidant Defense Systems In Inflammationmentioning
confidence: 99%